National emergency construction authority : communication from the President of the United States transmitting his notification of his declaration of a national emergency with respect to the threat of the national security and foreign policy of the United States caused by the invasion of Kuwait by Iraq, pursuant to 50 U.S.C. 1701 et seq., 1601 et seq., and 3 U.S.C. 301. (1991)
Summary goes here